This I Believe - Millen, Herbert E. (Tufts Archival Research Center, 2006)
Judge Millen describes how, despite his experience as a judge with the bad side of people, he still maintains an optimistic belief in the overall goodness of people, and while he still becomes discouraged and impatient with prejudice, his religion gives him comfort and support.